Fjendekærlighed og vennehad - Davidsen, Ole (Dansk Teologisk Tidsskrift, 2011)
“Love of Enemies, Hatred of Friends. Morality and Exchange in Luke 6:27-36” offers a semiotic interpretation of the radical lovecommand in the Sermon on the Plain. The love-command appears as a social paradox but is in no way semantically unreasonable. Its own rationality comes forth, when we uncover the semantic macro-cosmos of which it forms a part. Three different but structurally related realms can be identified therein: In the midpoint the Kingdom of Justice (love of friends, hatred of enemies) is flanked by the anarchistic Kingdom of Evil (hatred of friends) and the likewise anarchistic Kingdom of Mercy (love of enemies). Jesus’ love-command, representing the Kingdom of Mercy, receives its conciseness, rationality and intelligibility from being a structural permutation of constitutive elements in this semantic macro-cosmos which itself shows us the essential features of the narrative character of our moral thinking, based on a logic of exchange (giving and taking).